COVID-19 and Children's School Resilience: Evidence from Nigeria - Sylvain Dessy; Horace Gninafon; Luca Tiberti; Marco Tiberti (Global Labor Organization (GLO), 2021)
This paper analyzes the impact of COVID-19 lockdown measures on children's school resilience. Using an individual fixed-effect linear probability model on Nigeria data, it exploits the quasi-randomness of these measures to estimate their effect on school attendance after the lockdown was lifted. The results show that COVID-19 lockdown measures reduced children's probability of attending school after the school system reopened. This negative impact increased with children's age, reaching a peak among those whose education was no longer compulsory. For schoolchildren in that age group, the negative effect of COVID-19 lockdown measures is likely to be permanent, which, if not reversed, will undermine the quality of the economy-wide future labor force. The paper also finds evidence that, in the child marriageprone North-West part of Nigeria, these measures increased gender inequality in education among children aged 12 to 18. This result suggests that COVID-19 lockdown measures may exacerbate harmful traditional practices such as child marriage.
Keywords: C13; H52; I21; 330; COVID-19's lockdown measures; School attendance; Schools' disruptions; Gender inequality in education; Nigeria